FACTORS ASSOCIATED WITH THE USE OF IUD CONTRACEPTIVES AT THE PENDOPO EMPAT LAWANG PUBLIC HEALTH CENTER, INDONESIA - Mika Oktarina; Heni Angraini; Nuril Absari; Choralina Eliagita; Cholika Wulandari (Proceeding B-ICON, 2022)
The limited knowledge of women about contraception so that very few choose the IUD contraception. This study aims to determine the factors associated with the use of IUD contraceptives at the Pendopo Public Health Center, Empat Lawang Regency. The research population of all active family planning users who are in the Work Area of the Pendopo Health Center is 801 people. The sample in this study used purposive sampling as many as 89 people. Research analysis using Chi Square. The results showed there is a relationship between the level of education, knowledge, husband's support and there is no relationship between information from health workers and the use of IUD contraceptives with a moderate relationship category. It is hoped that health workers, especially midwives at the puskesmas, are expected to be able to provide more detailed counseling about contraceptives and evenly to all prospective acceptors